Strategic alliance for financing higher education in young demobilized (2016)
In a context of post-conflict and demobilized reintegrated into civilian life, higher education has an important role and must assume a challenge to formulate policies that allow finance access and retention in higher education and generate increases in coverage levels in the education system. Therefore this essay evaluates the relevance of a Strategic Alliance as a financing option for demobilized youth access to higher education from the concept of inclusive education and to be an alternative for efficient use of resources.